Incidental Intraductal Papillomas (<2 mm) of the Breast Diagnosed on Needle Core Biopsy do not Need to be Excised. Issue 2 (21st January 2013) - Jaffer, Shabnam; Bleiweiss, Ira J.; Nagi, Chandandeep
Abstract Most authors recommend excision of intraductal papillomas diagnosed on core needle biopsy. This leads to the question of whether or not excision is necessary for incidental intraductal papillomas on core needle biopsy as opposed to those corresponding to imaging findings. Using the pathology computerized data base we retrospectively identified 46 incidental intraductal papillomas diagnosed on core needle biopsy from 1/2000 to 12/2008. Clinical, radiologic, and pathologic information was gathered and correlated. All core needle biopsies were reviewed to confirm the diagnosis of incidental intraductal papillomas, and excision specimens reviewed when available. Of the 46 patients, follow‐up information was available in only 38. The age of the patients ranged from 39 to 82 years (mean = 48 years). Most incidental intraductal papillomas were diagnosed by mammotome core needle biopsy (36 cases). A total of 33 cases were performed for calcifications with the following indications: clustered = 21, new = 4, pleomorphic = 3, increasing = 3, indeterminant = 2. The correlating diagnoses included the following: fibrocystic changes with calcium phosphate = 18 or calcium oxalate = 10, fibroadenoma with calcifications = 5. The three masses were: two cases of cystic papillary apocrine metaplasia (I Ultrasound and 1 MRI) and 1 fibroadenoma (Ultrasound). In all cases, the intraductal papillomas were ≤0.2 cm, were not associated with calcifications, and were incidental to them or the underlying mass. A total of 14 patients underwent excision, whereas the remaining 24 have remained radiologically stable for over 12 months. The excision specimen findings were: fibrocystic changes = 8 and intraductal papilloma = 6. With the exception of one case, all the intraductal papilloma remained incidental to imaging findings. In this solitary case, the calcifications were described as pleomorphic and corresponded to fibrocystic changes calcifications on core needle biopsy. However, on excision, residual pleomorphic calcifications on mammogram correlated with both fibrocystic changes and intraductal papilloma. No cases were upstaged on excision to atypical duct hyperplasia or intraductal or invasive carcinoma. With the exception of one case, all incidental intraductal papillomas diagnosed on core needle biopsy were either completely excised or remained incidental. The exception occurred due to sampling error and accounted for the change from an incidental intraductal papillomas on core needle biopsy to one that was associated with calcifications on excision. Given the complete lack of upstaging, it is difficult to recommend excision of incidental intraductal papillomas diagnosed on core needle biopsy provided the index lesion has been adequately sampled and radiologic follow‐up is maintained.